KARAKTERISTIK PEMBINAAN KARAKTER RELIGIUS PADA SISWA SEKOLAH MENENGAH PERTAMA NEGERI 40 PALEMBANG - Suhasri, Anugerah Helen; Karoma, Karoma; Maryamah, Maryamah (JURNAL DARMA AGUNG, 2023)
Schools are educational institutions that have the responsibility to carry out character development because educational institutions not only aim to transfer knowledge from educators to students but also succeed in creating people with noble character. In this increasingly sophisticated era, society must be able to master science and technology so as not to be left behind by the times, various impacts and problems emerge, showing the deterioration of the nation's character and giving birth to unhealthy generations, so it is important to behave in accordance with religious principles in order to make a person behave. honest, kind and responsible. Religious character development also often teaches empathy, compassion, care and helps build a better community. When someone provides training regarding religious character, there are various programs, strategies or methods that can be used as a training process, especially at SMPN 40 Palembang which has made training efforts to develop students' religious character. The aim of this research is to analyze: (1) Characteristics of developing religious character in students at SMPN 40 Palembang (2) Implementation of religious character training in students at SMPN 40 Palembang (3) Religious character developed in students at SMPN 40 Palembang (4) Impact of training characteristics on the religious character of students at SMPN 40 Palembang. Location This research was conducted at SMPN 40 Palembang Jl HM Shaleh KM 7 Sukarami District using qualitative research, namely a case study type. Data was collected using interviews, observation and documentation methods. The data analysis used in the research includes data collection, data presentation, and drawing conclusions. Checking the validity of the data is carried out based on the criteria of degree of trust, transferability, dependency, certainty and triangulation. The results of this research show that the characteristics of religious character development for Palembang State Junior High School 40 students include a series of social skills development training, religious practices and attitude training for protecting the school environment which is included in the religious program, namely Social Skills Personal Development 40 with the approaches and methods used methods of habituation, discipline, counseling and example. This series of training produces a student's religious character which is reflected in accordance with religious values, including sincerity, trust and responsibility, discipline and compassion. By realizing a religious character that has religious values, the impact of the characteristics of building religious character on students at SMPN 40 Palembang produces a positive impact, this can be seen from the increase in students' spiritual awareness which is realized through the practice of worship and the realization of behavior according to character values. this is in a religious context